Managerial incentives and management forecast precision - CHENG, Qiang (Institutional Knowledge at Singapore Management University, 2013)
Managers have great discretion in determining forecast characteristics, butlittle is known about how managerial incentives affect these characteristics. This paperexamines whether managers strategically choose forecast precision for self-servingpurposes. Building on the prior finding that the market reaction to vague forecasts isweaker than its reaction to precise forecasts, we find that for management forecastsdisclosed before insider sales, more positive (negative) news forecasts are more (less)precise than other management forecasts. The opposite applies to managementforecasts disclosed before insider purchases. These results are consistent withmanagers strategically choosing forecast precision to increase stock prices beforeinsider sales and to decrease stock prices before insider purchases. Additional analysesindicate that the impact of managerial incentives on forecast precision is lesspronounced when institutional ownership is high or when disclosure risk is high, and ismore pronounced when investors have difficulty in assessing the precision of managers’information